2018
DOI: 10.3390/min8030117
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of CO2-Water-Mineral Interactions and Their Influence on the Permeability of Coking Coal and Implications for CO2-ECBM

Abstract: Abstract:Coal permeability is one of the most critical parameters affecting gas flow behavior during coalbed methane (CBM) production. However, little research has been conducted on how permeability evolves after CO 2 injection in coking coal. Hence, examining possible chemical interactions between coal minerals, water, and injected CO 2 can be very helpful to better characterize coking coal. In this study, coking coal specimens obtained from the Malan and Tunlan mines located in the Gujiao block of the Qinshu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…In future studies, for the CO 2 injection times and CO 2 injection well design, this study can be referred to. Meanwhile, attention should be paid to the permeability reduction effects [44,45]. The adsorption capacity of coal to CO 2 is 2-5 times higher than that of coal to methane [46,47].…”
Section: Future Studies For Co 2 Geo-sequestration In Coal Seamsmentioning
confidence: 99%
“…In future studies, for the CO 2 injection times and CO 2 injection well design, this study can be referred to. Meanwhile, attention should be paid to the permeability reduction effects [44,45]. The adsorption capacity of coal to CO 2 is 2-5 times higher than that of coal to methane [46,47].…”
Section: Future Studies For Co 2 Geo-sequestration In Coal Seamsmentioning
confidence: 99%
“…Therefore, the change in the pore morphology of coals, due to ScCO 2 exposure, during longer time scale has gained interest in recent years. Guo et al (2018) examined the interaction between ScCO 2 , H 2 O and coals for 5-6 months and found that the average pore diameter, porosity and microfracture of coals increased due to dissolution of calcite and dolomite. Particularly, S meso/mac and V meso/mac of all the coal samples were observed to increase by approximately 30-73% and 40-54%, respectively.…”
Section: Roughness Of the Pore Structurementioning
confidence: 99%
“…Thus, the pore structure of coals has been considered to get further enhanced (Li, 2018;Liu et al, 2018). Therefore, injecting CO 2 , H 2 S Source: reproduced with permission from Guo et al, 2018. and SO 2 fluid is considered to enhance the intensity of dissolution effect, thereby increasing the pore volume of coals and to mitigate the hazardous gaseous pollutants emitted into the atmosphere. With respect to secondary minerals, they are not considered to be precipitated, when the saturation index (SI), is less than zero.…”
Section: Mineral Dissolution and Precipitation Effectsmentioning
confidence: 99%
“…Furthermore, the H 2 O-induced swelling effect and blocking effect also have a profound impact on fluid migration. , Due to the unstable organic macromolecule structure of the coal matrix, H 2 O adsorbed on coal is able to trigger its volume expansion . Accordingly, the induced coal matrix swelling further compresses cleat space of the coal reservoir, resulting in decreasing porosity and permeability and further impeding adsorption, desorption, diffusion, and flow of CO 2 and CH 4 in the coal reservoir. , With regard to the latter effect, H 2 O retention in pores may block channels for CH 4 desorption from coal. , Particularly, H 2 O is capable of producing capillary force directed toward the fluid with the coal matrix via surface tension. Providing this pressure differential between inside and outside of the pore cannot overcome capillary force, and the permeability of the coal reservoir will decrease, thus making CH 4 desorption more difficult …”
Section: Introductionmentioning
confidence: 99%